Alarmin-activated B cells accelerate atherosclerosis after myocardial infarction via plasma cell-immunoglobulin dependent mechanisms. (25th November 2020) - Kyaw, T; Loveland, P; Kanellakis, P; Cao, A; Huang, A; Peter, K; Toh, B.H; Bobik, A
Abstract: Introduction: Myocardial infarction (MI) accelerates atherosclerosis and for years greatly increases the risk of recurrent cardiovascular events, such as stroke and MI. B cell-derived autoantibodies produced in response to MI also persist for years. Purpose: We investigated the role of B cells in adaptive immune responses to MI. Methods: We used an apolipoprotein-E-deficient (ApoE−/−) mouse model of MI-accelerated atherosclerosis to assess the importance of B cells using loss and gain of function approaches. In loss of function experiment, after inducing an MI we depleted B cells using an anti-CD20 antibody. Gain of function experiments involve transfers of purified MI-B cells from different donor mice, isolated one week after MI, into atherosclerotic ApoE−/− mice. Results: Depletion of B cells in MI mice prevented immunoglobulin G accumulation in plaques and MI-induced acceleration of atherosclerosis. Adoptive transfer of wildtype MI-B cells into atherosclerotic ApoE−/− mice greatly increased IgG accumulation in plaque and accelerated atherosclerosis in recipient mice. Cytokines that promote humoral immunity were also greatly increased in B cells activated by MI. These cells formed germinal centres within the spleen where they differentiated into antibody-producing plasma cells. Transfer of MI-B cells deficient in Blimp-1, the transcriptional repressor that drives their terminal differentiation to antibody-producing plasma cells failed to accelerate atherosclerosis in recipient mice. Alarmins released from infarcted heart were responsible for activation of B cells via toll-like receptors; transfer of MI-B cells deficient in MyD88, the canonical adaptor protein for inflammatory signaling downstream of toll-like receptors, prevented acceleration of atherosclerosis in recipient mice. Conclusion: Our data implicate early B cell activation and autoantibodies as a central cause for accelerated atherosclerosis post MI and identifies novel therapeutic strategies towards preventing recurrent cardiovascular events such as MI and stroke. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Health and Medical Research Council of Australia